Peace treaties : various treaties and agreements between the Allied and Associated Powers and the Serb-Croat-Slovene state, Roumania, Bulgaria, Hungary, and Turkey, together with certain other agreements signed by the Peace conference at Paris and Saint Germain-en-Laye. - Allied and Associated Powers (1914-1920), participant in a treaty.; Bulgaria, participant in a treaty.; Hungary, participant in a treaty.; Romania, participant in a treaty.; Turkey, participant in a treaty.; Yugoslavia, participant in a treaty. (Tufts University. Tisch Library., 2017)
1 online resource (448 pages); Presented by Mr. Lodge. Ordered printed April 25, 1921.; Tisch Outsourced Digitization 2017-10-02